Survivability of highly pathogenic avian influenza virus (H5N1) in naturally preened duck feathers at different temperatures. Issue 3 (28th March 2019) - Karunakaran, Athira Cheruplackal; Murugkar, Harshad V.; Kumar, Manoj; Nagarajan, Shanmugasundaram; Tosh, Chakradhar; Pathak, Anubha; Mekhemadhom Rajendrakumar, Arunraj; Agarwal, Rajesh Kumar
Summary: Ducks are the "Trojan Horses" for Asian H5N1 avian influenza viruses (AIV) and attain carrier status without displaying overt infection. These birds help in the spread of the virus among the poultry and human population through direct or indirect contact. Preen oil is the secretion of preen gland of water birds such as ducks. In a process called preening, the water birds spread preen oil across their feather and body. Preen oil has been known to play a significant role in the accumulation of various pathogens including Highly Pathogenic Avian Influenza (HPAI) from water onto feathers. However, the studies are scarce on the role of preen oil in the survivability of HPAIV. We conducted a simulative study to analyse the effect of preen oil on the survivability of the HPAI virus (H5N1) on duck feathers. Duck feather samples along with relevant controls were spiked with the H5N1 virus at two different initial concentrations (10 4 EID50 and 10 6 EID50 ), stored at 37°C, 25°C and 10°C temperatures and tested at regular intervals for percent infectivity by egg culture method and qRT‐PCR. The infectivity and viral load were significantly higher in naturally preened duck feathers in comparison to the three preen oil deficit controls at both low and high initial concentrations of virus (10 4 EID50 and 10 6 EID50 ). Maximum persistence was seen at 10°C in naturally preened duck feathers spiked with 10 6 EID50 concentration of viruses. It was also seen that depletion of preen oil from duck feathers reduced the persistence of the virus. These results demonstrate that preen oil plays a significant role in survivability and protection of HPAIV on duck feathers. This study herein will present new avenues in understanding one of the epidemiological niches of HPAIV.